Changes in population-level survival for advanced solid malignancies with new treatment options in the second decade of the 21st century - Pulte, Dianne; Weberpals, Janick; Jansen, Lina; Brenner, Hermann (Cancer, 2019)
BACKGROUND: Several new treatments that improve survival in clinical trials have been developed for various solid malignancies in advanced stages. The effect of these options on survival in the general population is currently unknown. - METHODS: Cancers for which 2 or more new treatment options have been approved by the US Food and Drug Administration during the years 2009 through 2011 for the treatment of advanced disease were identified, including adenocarcinoma of the lung, melanoma, breast cancer, prostate cancer, and renal cell carcinoma. Kaplan-Meier analysis was used to compare overall survival for these conditions in the Surveillance, Epidemiology, and End Results database for the periods 2007 to 2008, 2009 to 2010, and 2011 to 2012. Hazard ratios derived from adjusted, shared frailty models for cancer-specific survival were calculated as well for the years of diagnosis (2007-2008, 2009-2010, and 2011-2012). - RESULTS: Two-year survival increased for patients with advanced-stage lung adenocarcinoma (+3.0 percentage points), melanoma (+3.4 percentage points), and breast cancer (+2.7 percentage points). When only patients aged 15 to 64 years were included, 2-year survival for those with melanoma increased by +6.7 percentage points. No change in survival was observed for renal cell carcinoma. Decreases in the hazard ratio for cancer-specific mortality were observed during the period 2011 to 2012 compared with 2007 to 2008 for lung adenocarcinoma, melanoma, and breast cancer. - CONCLUSIONS: Small increases in 2-year survival were observed between the periods 2007 to 2008 and 2011 to 2012 for lung adenocarcinoma, melanoma, and prostate cancer. Cancer-specific mortality decreased for each of these cancers among patients who were diagnosed between the periods 2007 to 2008 and 2011 to 2013. These findings suggest that newer treatment options are beginning to increase survival for stage IV cancers at the population level.
Gesehen am 14.08.2019